Photocatalysis and the Origin of Life: Synthesis of Nucleoside Bases from Formamide on TiO₂(001) Single Surfaces - Senanayake, S. D.; Idriss, H. (Proceedings of the National Academy of Sciences - PNAS, 2006)
We report the conversion of a large fraction of formamide (NH₂CHO) to high-molecular-weight compounds attributed to nucleoside bases on the surface of a TiO₂ (001) single crystal in ultra-high vacuum conditions. If true, we present previously unreported evidence for making biologically relevant molecules from a C1 compound on any single crystal surface in high vacuum and in dry conditions. An UV light of 3.2 eV was necessary to make the reaction. This UV light excites the semiconductor surface but not directly the adsorbed formamide molecules or the reaction products. There thus is no need to use high energy in the form of photons or electrical discharge to make the carbon-carbon and carbon-nitrogen bonds necessary for life. Consequently, the reaction products may accumulate with time and may not be subject to decomposition by the excitation source. The formation of these molecules, by surface reaction of formamide, is proof that some minerals in the form of oxide semiconductors are active materials for making high-molecular-weight organic molecules that may have acted as precursors for biological compounds required for life in the universe.